Correlation between T and N Stages of Head and Neck Squamous Cell Carcinoma - Koirala, Krishna; Sinha, Bimal; Baskota, Dharma Kanta (Journal of College of Medical Sciences-Nepal, 2015)
Background and Objective: Squamous cell carcinoma of the head and neck region is a common pathological entity. Advanced primary lesion (T) and neck node metastasis (N) both are bad prognostic features for the carcinoma. Purpose of this prospective cross sectional study is to see if T stage of primary Head and Neck squamous cell carcinoma correlates with N stage of Neck node metastasis. Materials and Methods: Patients of all ages and both sex with biopsy proven squamous cell carcinoma of Head and Neck region were included in the study. After detailed history taking and clinical examination to identify the clinical T and N status of the disease, biopsy was taken from the primary site under local or general anesthesia. Fine Needle Aspiration Cytology (FNAC) of the palpable neck node (s) was performed. Correlation of T stage of the primary tumor was seen with that of N stage of the neck by applying the statistical tests. Results: There was significant correlation of the T status of the primary head and neck carcinoma with N status of the secondary neck. Conclusion: The T status of primary head and neck squamous cell carcinoma correlates with the N status of Neck in general. By knowing the T status of the primary tumor, we can predict the nodal status in most of the cases of head and neck carcinomas which can be used in planning the treatment modalities also. JCMS Nepal 2014; 10(4):26-31